2005
DOI: 10.1097/00129492-200501000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology of M??ni??re's Syndrome: Are Symptoms Caused by Endolymphatic Hydrops?

Abstract: Endolymphatic hydrops should be considered as a histologic marker for Meniere's syndrome rather than being directly responsible for its symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
342
1
5

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 478 publications
(362 citation statements)
references
References 36 publications
14
342
1
5
Order By: Relevance
“…Chermak and Dengerink 1987). This is supported by the findings in several other publications (Lindsay and Von Schulthess 1958;Lindsay et al 1967;Merchant 2010) where it was reported that only about 10 % of the cochleae from Ménière's disease patients (typically also suffering from tinnitus) showed significant loss of hair cells and cells of the spiral ganglion at the apex despite having all symptoms of Ménière's disease. Intense LF sound (30 Hz, 100 dB SPL, presented continuously for up to 24 h) has been shown to leave spiral ganglion cells intact and to not affect cochlear function in chinchillas (Harding et al 2007) 24 h post-exposure.…”
Section: Lf Sound-induced Transient Sound Perceptionssupporting
confidence: 71%
See 1 more Smart Citation
“…Chermak and Dengerink 1987). This is supported by the findings in several other publications (Lindsay and Von Schulthess 1958;Lindsay et al 1967;Merchant 2010) where it was reported that only about 10 % of the cochleae from Ménière's disease patients (typically also suffering from tinnitus) showed significant loss of hair cells and cells of the spiral ganglion at the apex despite having all symptoms of Ménière's disease. Intense LF sound (30 Hz, 100 dB SPL, presented continuously for up to 24 h) has been shown to leave spiral ganglion cells intact and to not affect cochlear function in chinchillas (Harding et al 2007) 24 h post-exposure.…”
Section: Lf Sound-induced Transient Sound Perceptionssupporting
confidence: 71%
“…Endolymphatic hydrops is the primary histopathological correlate of Ménière's disease, a condition affecting the inner ear and causing hearing loss, recurrent, spontaneous episodic vertigo, aural fullness and tinnitus (Monsell et al 1995). It is, however, unclear if endolymphatic hydrops represents cause or effect of Ménière's disease (Merchant et al 2005;Berlinger 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, nearly onethird of the cases of idiopathic hydrops show no association with the classic symptoms of Meniere's syndrome. 33 In addition, previous histopathological examinations have revealed that the contralateral ears of patients with unilateral Meniere's disease showed asymptomatic saccular hydrops in around 30% of patients. 34,35 Recently, Kato et al 36 reported that there was no significant association between the degree of EH and caloric responses, using MRI.…”
Section: Discussionmentioning
confidence: 98%
“…Histologically, Meniere's disease is characterized by endolymphatic hydrops and swelling of the endolymphatic space of the inner ear, 15 but the etiology and pathophysiology of endolymphatic hydrops are unknown. 16 Whether the swelling affects or injures the vestibular end organs is also unknown, but many patients with Meniere's disease have vestibular deficits as assessed by electronystagmography.…”
Section: Cell Viability and Availabilitymentioning
confidence: 99%